Structural behaviour of kenaf fiber as part shear reinforcement in oil palm shell reinforced concrete beams - Sayed Javid, Azimi (2015)
This thesis presents the structural behaviour of kenaf fibre as a part of shear reinforcement in oil palm shell reinforced concrete (OPS-RC) beams. The main objective of this research was to improve the structural properties of OPS-RC beams by incorporation of kenaf fiber for improving the structural properties of oil palm shell reinforced concrete (OPS-RC) beams. This investigation was carried out by using two methods; experimental and consequently numerical modelling. Experimentally five beams by incorporation of kenaf fiber with two shear reinforcement arrangements and three different amount of kenaf fiber were considered in this study. The first beam were constructed with full shear reinforcement and without fibre (SI = 0 % and with Vf = 0 %) denoted as a control beam. Meanwhile, two beams with full shear reinforcement (SI = 0 %) and with fibre volume fraction of Vf = 1 % and Vf = 2 % and two more beams with reduction of shear reinforcement (SI = 100 %) with fibre volume fraction of Vf = 1 % and Vf = 2 % were constructed respectively. The beam specimens were tested under four-point flexural test. Consequently numerical modelling with finite element method (FEM) software, Abaqus for calibration and validation of experiment results was considered. First, sensitivity analysis (mesh and time) was conducted to acquire the best correlation with the experimental result. Then, the experiments results of two beams with SI = 0 % and with Vf = 0 % and Vf = 1 % were used for calibration in FEM modelling investigation. Once satisfactory results were obtained parametric studies on key parameters with three shear reinforcement arrangement (SI = 0 %, SI = 50 % and SI = 100 %) and together with six volume fraction (Vf = 0 %, Vf = 0.5 %, Vf = 1 %, Vf = 1.5%, Vf = 2 % and Vf = 2.5 %) of kenaf fiber were carried out. The results comparison showed that there is a good agreement between the experimental test and nonlinear finite element analysis NLFEA results. Generally this investigation demonstrated up to 37 % improvement on structure properties of OPS-RC beam by addition of kenaf fiber.